Wearable IoT for Maternal Healthcare: A Literature Review on Implementation, Challenges, and Future Prospects - Sulisworo, Dwi; Erviana, Vera Yuli; Rosyady, Phisca Aditya; Astuti, Dhesi Ari; Rasyid, Erwin; Warsiti; Bakhtiar, Rahmat; Ismail, Sjarif; Duma, Krispinus (Bincang Sains dan Teknologi, 2025)
Wearable Internet of Things (IoT) devices for pregnant women have emerged as a significant innovation in healthcare. This technology enables real-time monitoring of maternal and fetal health, providing data that facilitates faster and more accurate medical decision-making. This article presents a literature review on the development and implementation of wearable IoT for pregnant women and its impact on healthcare services. The study identifies various types of wearable devices, monitored health parameters, and the technical and ethical challenges associated with their use. The findings reveal that wearable IoT can enhance healthcare quality through early detection of pregnancy complications, improved efficiency of medical personnel, and reduced healthcare costs. However, issues such as data privacy, device sustainability, and technological disparities remain major challenges that require further attention. This review provides valuable insights for technology developers, healthcare providers, and researchers to maximize the potential of wearable IoT in supporting maternal health holistically.